Spinal subarachnoid haematoma after neuraxial anaesthesia in a patient with polycythaemia vera. Issue 1 (12th January 2021) - Martins, T.; Montenegro, L.; Silva, A.; Reis, H.; Pereira, E.; Lucas, P.
Summary: Polycythaemia vera is a common haematological proliferative disorder. It is characterised by uncontrolled red cell production with ensuing peri‐operative vaso‐occlusive and haemorrhagic complications. Spinal haematoma after neuraxial anaesthesia is rare; most cases are associated with technical difficulties or bleeding disorders. Current consensus opinion suggests that neuraxial anaesthesia in patients with polycythaemia vera is safe due to a lower risk of thrombotic events and hypoxaemia compared with general anaesthesia. We report a case of a spinal subarachnoid haematoma after uneventful neuraxial anaesthesia in a patient with optimised polycythaemia vera. Despite an emergent laminectomy, the patient developed permanent motor deficits. This report highlights that although neuraxial anaesthesia is recommended by many authors, patients with polycythaemia vera can paradoxically have an increased haemorrhagic risk from platelet dysfunction and acquired von Willebrand disease. Clinicians proceeding with surgery under neuraxial anaesthesia should appreciate these risks even in patients with normal or apparently elevated thrombotic states. This case also demonstrates that traditional coagulation tests may need to be complemented by pre‐operative platelet function tests and screening for von Willebrand disease. Finally, the importance of the patient participation in the choice of the anaesthesia technique cannot be understated, with specific attention paid to this frequently unrecognised risk.